A Phenomenal Rise of the Indian Paralympians in the 21st Century - Singh, Anidev (Πανεπιστήμιο Πελοποννήσου, 2024)
The study examined the rise in the Indian Paralympians in the 21st century. The performance of Indian Paralympians at Tokyo 2020 Paralympics games surpassed the joint performance of Indian Para-athletes in all previous Paralympics combined. The objectives of the study were to study the rise of Indian Paralympians and the factors responsible for the same. The study also listed down the challenges and future plans & suggestions for the growth and development of Indian Paralympians. The review of related literature highlighted the growth of Paralympics movement in India and around the world. It also suggested the role of Government policies and change in the perception of the society in regard to Para-athletes and Para-sports. The qualitative research method comprised of Semi structure interviews was employed on 6 samples for the data collection and the same was analysed using thematic analysis method. The results suggested a rise in the performance of the Indian Paralympians in the 21st century. The responses suggested the factors responsible for the rise in the performance of the Paralympians and para-sports in India. The role of social media was also emphasized in the promotion of para sports in India. The participants appreciated the efforts of Indian government in uplifting the status of Paralympians and Para-sports in India. They also stated that more support is required from the private organisations in term of funding, sponsorship and job opportunities. The participants also highlighted the challenges faced by the para-athletes and various suggestions & future plans to sustain the development of Indian Para sports at the grassroot and international level. The participants talked about the various societal issues and need of more awareness programs especially in the rural areas. In the end, the participants suggested future plans for the sustained development of the para sports in India.
Keywords: Παραολυμπιακό κίνημα - Ινδία; Παραολυμπιακοί Αγώνες; Παραολυμπιονίκες - Ινδία; Κυβερνητική πολιτική - Ινδία; Αθλητική χορηγία; Μέσα μαζικής ενημέρωσης και αθλητισμός - Κοινωνικές απόψεις - Ινδία; Χρηματοδότηση - Ινδία; Paralympic movement - India; Paralympic Games; Paralympians - India; Government policy - India; Sports sponsorship; Mass media and sports - Social aspects - India; Finance - India; Disability; Paralympians; Para-sports; Paralympics; Performance